Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_277_286
|View full text |Cite
|
Sign up to set email alerts
|

Solute Redistribution during Planar and Dendritic Growth of Directionally Solidified Ni-Base Superalloy CMSX-10

Abstract: The solute redistribution behavior during directional solidification of the alloy CMSX-10 with planar and dendritic solid/liquid (S/L) interfaces has been investigated by directional solidification and quenching (DSQ) technique. In particular, the elemental partitioning coefficient during the solidification of primary γ and γ/γ′ eutectic was quantitatively estimated by electron probe microanalysis (EPMA) on the sample quenched during planar growth of primary γ and γ/γ′ eutectic, respectively. The EPMA composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…the solidification of IDP was also influenced by solute back diffusion. This result agrees with Liu's study (G = 250 K/cm, V = 10-500 lm/s) [30], but is different from the research on CMSX-10 (G = 138 K/cm, V = 5-100 lm/s) [33], which might be ascribed to the relatively low withdrawal rates in the literature [33]. The influence of withdrawal rate on interlamellar spacing of eutectic (k) is also shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…the solidification of IDP was also influenced by solute back diffusion. This result agrees with Liu's study (G = 250 K/cm, V = 10-500 lm/s) [30], but is different from the research on CMSX-10 (G = 138 K/cm, V = 5-100 lm/s) [33], which might be ascribed to the relatively low withdrawal rates in the literature [33]. The influence of withdrawal rate on interlamellar spacing of eutectic (k) is also shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…Recently, Seo et al [16] showed that Scheil solidification occurs during the solidification of primary c with planar S/L interface in CMSX-10. Compared to the DS with planar S/L interface that exhibits Scheil solidification, the diffusion distance is as small as a scale of dendrite arm spacing in dendritic solidification, which may give rise to the decrease in interdendritic microsegregation by solidstate back-diffusion.…”
Section: Effect Of Back-diffusion and Dendrite Arm Coarseningmentioning
confidence: 98%
“…the microsegregation would be negligible depending on the diffusivity of each solute element when the cooling rate is increased up to a certain limit. [16,30,33,34] The back-diffusion effect with respect to the cooling rate in CMSX-10 and CMSX-4 can be qualitatively evaluated on the basis of c/c¢ eutectic volume fraction, because all the c¢ forming elements in both alloys were found to be segregated to liquid during the solidification of primary c (Table II). Figure 10 shows a schematic illustration of the back-diffusion effect on the formation of c/c¢ eutectic, which is based on the quasi-binary Scheil model.…”
Section: Effect Of Back-diffusion and Dendrite Arm Coarseningmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid/liquid interface has planar morphology due to the slow solidification rate, 0.5 µm/s. The chemical composition at the solid/liquid interface of the DSQ specimen is comparable to the composition when solidification is begun, since the DSQ specimen was quenched in the middle of solidification [13,14]. Therefore, EPMA analysis was carried out on a cross-section of the solid/liquid interface in order to calculate the partition coefficient.…”
Section: Solute Partitioning Characteristics During Solidificationmentioning
confidence: 99%